Health outcomes among detoxification patients: The role of chronic pain. Issue 4 (4th May 2021) - Woodhead, Erin L.; Brief, Deborah; Below, Maureen; Timko, Christine
Abstract: Understanding associations between chronic pain and health outcomes among detoxification patients may help improve treatment outcomes and abstinence rates. Exercise is a modifiable lifestyle factor that may reduce the effect of pain on outcomes in this population. The current study examined whether baseline pain, exercise, and their interaction were associated with psychiatric and medical severity, and abstinence self‐efficacy, over six months following detoxification. Participants were veteran patients in alcohol or opioid detoxification treatment ( N = 298) who were followed for six months (91.1%). Psychiatric severity and abstinence self‐efficacy improved over the six months after detoxification; medical severity was stable. More intense pain at baseline was associated with poorer psychiatric and medical outcomes during the post‐detoxification period. Regular exercise at baseline was associated with less psychiatric severity and more abstinence self‐efficacy during the post‐detoxification period. A significant pain by exercise interaction at baseline indicated that regular exercise was associated with more abstinence self‐efficacy during the post‐detoxification period only among participants with less intense pain. Pain by exercise interactions was not significant for the outcomes of psychiatric and medical severity. Among detoxification patients, exercise may be beneficial in improving outcomes among those with less intense pain.